Effect of rhizome extract of Acorus calamus on depressive condition induced by forced swimming in mice - Ilaiyaraja N,; Dongzagin Singsit,; Farhath Khanum, (International Journal of Phytomedicine, 2012)
The present study evaluated the anti-depressant properties of A. calamus rhizome in a forced swimming test (FST) of mice model. Three doses of methanol extract of rhizome (200,400 and 600 mg extract/kg b.wt) and imipramine (15 mg/kg b.wt), a positive control, were orally administered once a day for the consecutive period of 14 days in Balb/c mice. The effect of extract on immobility period was measured using forced swimming test. The levels of cortisol monoamine oxidase and neurotransmitters were analyzed using standard methods. The anti-depressant effect was observed maximum at the dose of 200 mg/kg. b.wt that caused 23.82% reduction in immobility period. The extract also significantly attenuated the FST-induced elevation of plasma cortisol, monoamine oxidase activity and returned the altered levels of neurotransmitters near to the normal levels in brain. These results of the present study suggest that the extract of A. calamus rhizome has antidepressant-like activity which is mediated by modulating the central neurochemical as well as HPA (hypothalamicpituitary-adrenal) axis in response to stress induced by FST. Therefore, A.calamus rhizome may be used as a valuable herbal supplement for the treatment of depression related conditions.